(3cja JYed GdHhQUI? (B:s (3Odjd GdeSJKeQ GdUZjQ (B/s - (3HjcjJ, eGjcds ((3GdbGgQI(B: s (3OGQ GdaGQhb ddfTQ(B, s, 2006)
(3GdCSge(B- (3CfhGY GdChQGb GdeGdjI GdCNQi(B- (3GdSfOGJ GdMchejI GdeVehfI(B- (3COhGJ GdESJKeGQ GdaQYjI(B- (3GdGSge GdNGQLjI(B- (3GdGSge hTQcGJ GdESJKeGQ(B- (3CgejI GdUaMGJ GdeGdjI HGdUMa hGdeLdGJ(B- (3cjajI GNJjGQ GdGSge GdLOjOI(B- (3cjajI JMOjO hbJ TQGA GdGSge(B- (3GdHhQUGJ GdHQjWGfjI(B- (3GdHhQUGJ GdCNQi(B- (3Mbhb hhGLHGJ GdeSGgejf(B- (3Mbhb GdEcJJGH hGdCSge GdeLGfjI(B- (3HjY CSge GdTQcGJ(B- (3GdVQGFH(B.s
Keywords: (3GdChQGb GdeGdjIs; (3GdHhQUIs